Research on the cold charging performance of refrigerated truck accumulator plate based on heat pipe heat transfer - HUANG Jiexuan; WANG Qiang; HUI Xiaoyang; WANG Da; TAN Shengxuan (Shipin yu jixie)
ObjectiveTo improve the cold charging efficiency of cold plate type refrigerated logistics vehicles and optimize the structural parameters of heat pipe type cold storage plate.MethodsA mathematical-physical model was established for heat pipe accumulator plate to simulate and study the cooling process of the plate under different inlet flow rates of refrigerant and heat pipe diameters, and to compare with the experimental results.ResultsThe results of the simulation study were in good agreement with the experimental results, and the average temperature error of the accumulator was 0.28 ℃ in the process of cold charging. When the inlet flow rate of the refrigerant was 1 m/s and the diameter of the heat pipe was 10 mm, the cold charging performance of the accumulator plate was optimal, and the complete freezing time of the accumulator plate at this time was 74 min, with the resistance loss of 1 567.4 Pa, and the cold charging efficiency was 1.2×105 mm3/min.ConclusionThe test-optimised heat pipe accumulator plate structure can effectively improve the cold charging efficiency of the accumulator plate, shorten the cold charging time and reduce the energy consumption of cold charging.